Correlates of caregiver well-being: The National Study of Caregivers - Parr, Lydia C.; Mielenz, Thelma J. (Frontiers in Public Health, 2023)
Background The literature demonstrates an association between aspects of caregiving and support with caregiver burden and differences by race. Our objective was to examine correlates of caregiver wellbeing, and if the effect is moderated by race. Methods The National Study of Caregiving (NSOC) is a survey of unpaid and familial caregivers affiliated with participants in the National Health and Aging Trends Study, a nationally representative survey of Medicare beneficiaries. A total of 899 participants were examined cross-sectionally with logistic and multinomial logistic regression models to obtain adjusted odds ratios (aOR) and 95% confidence intervals (CI) for NSOC Round 3 (2017), stratified by race, to determine the association between aspects of caregiving and support variables with the two outcomes, three-level caregiving gains, and response to the statement “life has meaning and purpose.” Results Among black caregivers with no family or friends to help, there were lower gains compared to very high gains (aOR: 2.82, 95% CI: 1.18, 6.77). Black and white caregivers who endorsed lower ratings regarding being appreciated by the care recipient had lower gains for “life has meaning and purpose” (aOR: 2.46, 95% CI: 1.00, 6.02; aOR: 1.65, 95% CI: 1.06, 2.56). Black caregivers with lower ratings regarding being appreciated had lower gains compared to very high gains (aOR: 5.04, 95% CI: 1.48, 17.17). White caregivers endorsing lower ratings to the same question had lower gains compared to very high gains (aOR: 3.27, 95% CI: 1.77, 6.04), and those with more help had lower gains (aOR: 0.81, 95% CI: 0.70, 0.93). Conclusion The relationship between various correlates and positive aspects of caregiving is moderated by black and white races. Further study on the impact of aspects of caregiving and support networks for caregivers may shed light on factors contributing to racial differences and areas for intervention.